6,7-Dihydroxy-2-(4′-hydroxyphenyl)naphthalene induces HCT116 cell apoptosis through activation of endoplasmic reticulum stress and the extrinsic apoptotic pathway - Chiu CF; Lai GY; Chen CH; Chiu CC; Hung SW; Chang CF (Dove Medical Press, 2019)
Ching-Feng Chiu,1–3 Guan-Ying Lai,4 Chung-Hwan Chen,5–7 Chien-Chao Chiu,8 Shao-Wen Hung,8,9 Chi-Fen Chang10 1Graduate Institute of Metabolism and Obesity Sciences, College of Nutrition, Taipei Medical University, Taipei 11031, Taiwan; 2TMU Research Center of Cancer Translational Medicine, Taipei Medical University, Taipei 11031, Taiwan; 3TMU Research Center of Cancer Translational Medicine, Taipei Medical University, Taipei, Taiwan; 4Master Program for Pharmaceutical Manufacture, China Medical University, Taichung 40402, Taiwan; 5Department of Orthopedics, Kaohsiung Municipal Ta-Tung Hospital, Kaohsiung Medical University, Kaohsiung 80145, Taiwan; 6Department of Orthopedics, Kaohsiung Medical University Hospital, Kaohsiung Medical University, Kaohsiung 80708, Taiwan; 7Orthopaedic Research Center, Kaohsiung Medical University, Kaohsiung 80708, Taiwan; 8Division of Animal Industry, Animal Technology Laboratories, Agricultural Technology Research Institute, Xiangshan, Hsinchu 300, Taiwan; 9Nursing Department, Yuanpei University, Xiangshan, Hsinchu 300, Taiwan; 10Department of Anatomy, School of Medicine, China Medical University, Taichung 40402, Taiwan Background: Colorectal cancer is the third leading cause of cancer-related deaths worldwide, and therefore, the development of novel drugs for its prevention and therapy are urgently required. This study aimed to determine the molecular mechanism of 6,7-dihydroxy-2-(4'-hydroxyphenyl)naphthalene (PNAP-6)-induced cytotoxicity in human colorectal cancer (HCT116) cells.Methods: The effects of 2-phenylnaphthalene derivatives on HCT116 cell growth and viability were assessed by MTT assays. The mechanisms involved in the regulation of the extrinsic apoptosis and endoplasmic reticulum (ER) stress pathways by PNAP-6 were analyzed by annexin-V/propidium iodide flow cytometric analysis, Hoechst 33342 fluorescent staining, and Western blotting.Results: PNAP-6 was shown to have an IC50 value 15.20 µM. It induced G2/M phase arrest in HCT116 cells, associated with a marked decrease in cyclin B and CDK1 protein expression and increased caspase activation, PARP cleavage, chromatin condensation, and sub-G1 apoptosis. Moreover, we found that the apoptotic effects of PNAP-6 proceeded through extrinsic apoptosis and ER stress pathways, by increasing the expression of Fas protein and ER stress markers, including PERK, ATF4, CHOP, p-IRE1α, and XBP-1s.Conclusion: These results suggest that 2-phenylnaphthalene derivatives, such as PNAP-6, have potential as new treatments for colorectal cancer. Keywords: colorectal cancer, endoplasmic reticulum stress, extrinsic apoptosis pathway, 2-phenylnaphthalenes